W kręgu lwowskich artystów i uczonych. Album autografów Witołda Bartoszewskiego (PDF 2,82 MB) (Książnica Śląska, 2025)
The author presents one of the most valuable manuscripts of the Biblioteka Śląska w Katowicach – the 19th-century Album autografów,once belonging to the secretary of the Koło Literacko-Artystycznein Lwów, Witold Bartoszewski. The Album contains autographs ofwriters, artists, politicians and scholars, e.g. Jan Kasprowicz, MariaKonopnicka, Adam Asnyk and Michał Bałucki. The text introducesthe owner of the Album and explains the circumstances of the creation of individual entries.